Urgensi Menjadi Teladan: Peran Guru Sebagai Role Model Dalam Pendidikan Agama Islam - Adib, M. Afiqul (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
Islamic Religious Education plays a central role in shaping individuals' character and morality. In this context, teachers not only act as educators but also as role models who provide real-life examples for students. This article explores the urgency of being a role model in Islamic religious education, focusing on the role of teachers as role models. Through a qualitative approach, this research examines the concept and implications of being a role model in the context of Islamic religious education. In this context, the teacher's role extends beyond imparting religious knowledge to demonstrating consistent religious practices aligned with Islamic values. Teachers' role modeling can influence students' character formation, helping them understand and apply Islamic teachings in their daily lives. The article also discusses the challenges and strategies in being an effective role model, as well as its practical implications in the context of Islamic religious education in the modern era. By strengthening the teacher's role as a good role model, Islamic religious education can significantly contribute to shaping a generation with high morality and noble character.